Bridging the genomic data gap in Africa: implications for global disease burdens - Olabode Ebenezer Omotoso; John Oluwafemi Teibo; Festus Adebayo Atiba; Tolulope Oladimeji; Ayomide Oluwadarasimi Adebesin; Ahmad O. Babalghith (BMC, 2022)
Abstract This paper highlights the gap in the use of genomic data of Africans for global research efforts for disease cures. Genomic data represents an important tool used in disease research for understanding how diseases affect several populations and how these differences can be harnessed for the development of effective cures especially vaccines that have an impact at the genetic level e.g., RNA vaccines. This paper then provides a review of global genomic data status where three continents are reported to be the major contributor of genomic data to repositories used for disease research and the development of vaccines and medicines around the world. We reviewed the most recently published information about genetic data inclusiveness of populations, explaining how genomic data of Africans is lacking in global research efforts that cater towards the eradication of pandemics via the development of vaccines and other cures. We also discuss the implication of this non-inclusiveness for global disease burdens and indicate where changes need to be made in the last part of the paper. Lastly, the entire centers on some general policy recommendations to fully include African genomic data in such global genetic repositories. These recommendations can be implemented in African countries to improve genetic data collection, storage, and usage policies.